Efficiency Control in Iridium Complex-Based Phosphorescent Light-Emitting Diodes. (10th July 2012) - Diouf, Boucar; Jeon, Woo Sik; Pode, Ramchandra; Kwon, Jang Hyuk
Abstract : Key factors to control the efficiency in iridium doped red and green phosphorescent light emitting diodes (PhOLEDs) are discussed in this review: exciton confinement, charge trapping, dopant concentration and dopant molecular structure. They are not independent from each other but we attempt to present each of them in a situation where its specific effects are predominant. A good efficiency in PhOLEDs requires the triplet energy of host molecules to be sufficiently high to confine the triplet excitons within the emitting layer (EML). Furthermore, triplet excitons must be retained within the EML and should not drift into the nonradiative levels of the electron or hole transport layer (resp., ETL or HTL); this is achieved by carefully choosing the EML's adjacent layers. We prove how reducing charge trapping results in higher efficiency in PhOLEDs. We show that there is an ideal concentration for a maximum efficiency of PhOLEDs. Finally, we present the effects of molecular structure on the efficiency of PhOLEDs using red iridium complex dopant with different modifications on the ligand to tune its highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energies.